OLDEST STEM TELEOSTEI FROM THE LATE LADINIAN (MIDDLE TRIASSIC) OF SOUTHERN CHINA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
The origin of the largest modern vertebrate group, the Teleostei, saw major refinements in the last decades, thanks to newly discovered and stratigraphically closely spaced Triassic Lagerstätten. Here we report the oldest Pholidophoriformes (stem teleosts) that were collected during a large scale yet detailed excavation of Upper Ladinian (Middle Triassic) marine deposits in Xingyi City, Guizhou Province, China. Taxonomic comparisons support the erection of a new pholidophorid genus, Malingichthys gen. nov., with two species. The new genus shows a partially fused skull roof, a preopercular bone with a hockey-stick shape and, for the first time in Pholidophoridae, supraneural elements. Most Triassic marine vertebrate clades (fishes and reptiles, Malingichthys included) first emerged in the South China Block, with Late Ladinian most showing an important faunal transformation that was strengthened by our last findings. The material here described is about 2 million years older than the previous records for pholidophorids.
Keywords: New taxa; Pholidophoriformes; Ladinian; Teleostean origin; Guizhou